NJL-type models in the presence of intense magnetic fields: The role of the regularization prescription - Avancini, Sidney S. (2019)
We study the regularization dependence of the Nambu-Jona-Lasinio model (NJL) predictions for some properties of magnetized quark matter at zero temperature (and baryonic density) in the mean field approximation. The model parameter dependence for each regularization procedure is also analyzed in detail. We calculate the average and difference of the quark condensates using different regularization methods and compare with recent lattice results. In this context, the reliability of the different regularization procedures is discussed.